2021
DOI: 10.3389/fpls.2021.776972
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Verification of Cold Tolerance Genes in Spring Maize Seedlings Based on a Genome-Wide Association Study and Quantitative Trait Locus Mapping

Abstract: Maize (Zea mays L.) is a tropical crop, and low temperature has become one of the main abiotic stresses for maize growth and development, affecting many maize growth processes. The main area of maize production in China, Jilin province, often suffers from varying degrees of cold damage in spring, which seriously affects the quality and yield of maize. In the face of global climate change and food security concerns, discovering cold tolerance genes, developing cold tolerance molecular markers, and creating cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Therefore, chilling susceptibility in maize crop is one of the major concerns for optimum yield, which is drastically reduced when the plant is subjected to early-stage cold stress [6,7]. Although much work has been done to understand the biological mechanisms behind cold tolerance [8][9][10], there is a lack of studies addressing the metabolic responses resulting in increased/decreased tolerance levels in maize.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chilling susceptibility in maize crop is one of the major concerns for optimum yield, which is drastically reduced when the plant is subjected to early-stage cold stress [6,7]. Although much work has been done to understand the biological mechanisms behind cold tolerance [8][9][10], there is a lack of studies addressing the metabolic responses resulting in increased/decreased tolerance levels in maize.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have reported that low-temperature stress during critical growth stages in major cereals significantly reduces the photosynthetic rate of plants, causing accumulation of carbohydrates which leads toward altered hormonal contents and enzyme activities ( Wang et al, 2017 ; Liu et al, 2019 ; Yan et al, 2022 ). For optimized plant metabolic and energy transformation processes, photosynthesis is the essential source, however, it is greatly sensitive to abiotic stresses ( Shah et al, 2020b ), such as drought and high- and low-temperature stresses ( Jin et al, 2021 ; Zhang et al, 2022 ). Spring low-temperature stress and other abiotic stress of such heavy metals impose oxidative damages ( Ahmad et al, 2021a ) and majorly impact the growth and development processes of plants by affecting important morphological and physiological processes, and then dry-matter accumulation and distribution, which subjects toward reduction in crop production, quality, and ultimately food security ( Nurhasanah Ritonga and Chen, 2020 ; Aazami et al, 2021 ; Ahmad et al, 2021b ).…”
Section: General Background and Climate Change Statusmentioning
confidence: 99%
“…These authors further verified the two QTLs using transcriptome data and identified 13 candidate genes likely to be involved in controlling the cold responses. Recently, Jin et al ( 2021 ) studied cold responses in maize using a joint analyses that combined QTL and GWAS. They first performed QTL mapping for POD activity using an F 2:3 population (210 lines) derived from cold-tolerant (W10) and cold-sensitive (W72) lines, and detected 12 QTLs significantly associated with POD activity and cold tolerance.…”
Section: Genetic and Genomic Approaches To Dissect Cold Tolerance In ...mentioning
confidence: 99%
“…In recent years, joint analysis using advanced populations or genomic tools has become increasingly popular to narrow down the search for candidate genes. Such an approach was recently used successfully to identify the major-effect cold regulating gene Zm00001d002729 (Jin et al, 2021 ), suggesting that it can be more widely applied in other studies.…”
Section: Genetic and Genomic Approaches To Dissect Cold Tolerance In ...mentioning
confidence: 99%